Peritoneal Fluid Trefoil Factor-3 Peptide Levels and Associated Factors in Chronic Peritoneal Dialysis Patients - AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2018)
OBJECTIVE: TFF3 is a small peptide hormone secreted from mucous producing cells and many epithelial cells. TFF3 inhibits apoptosis, promotes migration and facilitates restoration against injury. In our cross-sectional study, TFF3 levels in peritoneal fluids of peritoneal dialysis (PD) patients were measured and associated factors were investigated. MATERIAL and METHODS: Peritoneal fluid after a 12-hour dwell and concurrent serum samples of 48 chronic PD patients were collected. Serum and peritoneal fluid TFF3 levels were measured by ELISA. The SPSS15.0 package was used for statistical analysis of database files. RESULTS: The study included 48 patients (men/women; 24/24, mean age: 51.6813.9 years) with a median PD vintage of 43 months (3-200). Median effluent TFF3 level was 17.07 ng/ml (2.38-99.4). There was no relationship between the number of peritonitis episodes and TFF3 levels. There was a positive correlation between effluent TFF3 levels and PD vintage (r=0.349, p<0.015). There was also a positive correlation between effluent TFF3 and serum PTH. Median serum TITS was 1.56 ng/ml (0.79-11.05). There was no association between serum TFF3 levels and clinical features. After multivariate analysis, the only association was between effluent TFF3 and PD vintage. CONCLUSION: Effluent TFF3 levels increasing with dialysis vintage may be related to local production or peritoneal transport.
Keywords: Chronic kidney disease; Peritoneal dialysis; Peritoneal fluid; Trefoil-Factor3; KIDNEY-DISEASE; EXPRESSION; INJURY; SERUM